2022
DOI: 10.1371/journal.pone.0278027
|View full text |Cite
|
Sign up to set email alerts
|

Repositioning of acefylline as anti-cancer drug: Synthesis, anticancer and computational studies of azomethines derived from acefylline tethered 4-amino-3-mercapto-1,2,4-triazole

Abstract: Novel azomethines derived from acefylline tethered triazole hybrids (7a-k) have been synthesized and evaluated against human liver cancer cell line (Hep G2) using MTT assay. The synthesized series of azomethines exhibited promising efficacy against liver cancer cell line. Screening of the synthesized series identified compound 7d with the least cell viability value (11.71 ± 0.39%) as the most potent anticancer agent in contrast to the reference drug acefylline (cell viability = 80 ± 3.87%). In this study, the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 33 publications
(25 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…The LigPrep module [30] is used for preparation of the molecules once the protein preparation module [31] has finished preparing the protein. The Glide ligand docking tool is used to interact the generated proteins and molecules with one another [32] . To analyze the effects and effects of the researched compounds on human metabolism, the Qik‐prop module of the Schrödinger program [33] was employed while doing the ADME/T analysis (absorption, metabolism, distribution, toxicity, and excretion).…”
Section: Methodsmentioning
confidence: 99%
“…The LigPrep module [30] is used for preparation of the molecules once the protein preparation module [31] has finished preparing the protein. The Glide ligand docking tool is used to interact the generated proteins and molecules with one another [32] . To analyze the effects and effects of the researched compounds on human metabolism, the Qik‐prop module of the Schrödinger program [33] was employed while doing the ADME/T analysis (absorption, metabolism, distribution, toxicity, and excretion).…”
Section: Methodsmentioning
confidence: 99%
“…First, the molecules are optimized in the gaussian software program, then the LigPrep module [54] is prepared for calculations using optimized structures. The Glide ligand docking module [55] was used to examine the interactions between the molecules and the cancer protein after preparation. Calculations were made using the OPLS4 method in all calculations.…”
Section: Methodsmentioning
confidence: 99%
“…Due to their substantial applications across industries, including biological, agricultural, medicinal and pharmacological fields, chemists have drawn their attention to various heterocyclic scaffolds, such as piperazines (Halimehjani et al, 2022), benzoxazole, benzothiazole (Zou et al, 2023), heterocyclic sulfonamides (Apiraksattayakul et al, 2022), benzofurans (Farhat et al, 2022), benzimidazoles (Nardi et al, 2023), thiadiazoles (Janowska et al, 2020), pyarzoles (Nazeer et al, 2023), lamivudines (Henriquez-Camacho et al, 2023), ciprofloxacin-based acetanilides (Zhang et al, 2018), triazoles (Irfan et al, 2024), quinoxalines (Montana et al, 2019), and oxadiazoles (Kerru et al, 2020;Irfan et al, 2022;Irfan et al, 2023). Notably, theophylline (Shahzadi et al, 2020;Shahzadi et al, 2022a), a naturally occurring methylxanthine, has found frequent therapeutic use in treating conditions such as asthma, respiratory deficits in premature infants, and chronic pulmonary obstructive disease (COPD). It also functions as a phosphodiesterase inhibitor (Ito et al, 2002;Saharan and Nantwi, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…It also functions as a phosphodiesterase inhibitor (Ito et al, 2002;Saharan and Nantwi, 2006). Acefylline (Shahzadi et al, 2022b), a derivative of theophylline with pharmacological activity, serves various purposes, including bronchodilation, heart stimulation, diuresis, smooth muscle relaxation, antimicrobial and antituberculosis properties, and antiinflammatory effects (Foppoli et al, 2007;Mangasuli et al, 2018;Gopinatha et al, 2020;Shahzadi et al, 2020;Shahzadi et al, 2022a;Montaño et al, 2022), as illustrated in Figure 1.…”
Section: Introductionmentioning
confidence: 99%